Translation and Psychometric Properties of Bedtime Procastination Scale (BPS) in Peruvian College Studentsand Psychometric Properties of Bedtime Procastination Scale (BPS) in Peruvian College Students - Franco-Jimenez, Rulman Andrei (2025)
The purpose of this study was to translate the Bedtime Procrastination Scale (BPS) into Spanish and to evaluate its psychometric properties. A sample of 419 students from three Peruvian universities participated in the study. Confirmatory factor analysis was conducted to evaluate the original model of the scale, which initially showed poor fit indices. Improved fit indices were obtained after removing reverse-scored item, χ²(5) = 9.240, CFI = .998, RMSEA = .045, TLI = .997, and SRMR = .013. The internal consistency of the scale, examined using the omega coefficient, was found to be satisfactory (ω = .86). Moreover, measurement invariance analysis supported gender invariance, indicating that the scale functions equivalently across male and female participants. Additionally, convergent validity was assessed by examining the correlations between the BPS and insomnia, as measured by the Athens Insomnia Scale (AIS-5), revealing a moderate correlation (r = .44). In summary, the Spanish translation of the BPS demonstrated adequate psychometric properties in Peruvian college students and supported a one-factor structure after the removal of reverse-scored items.